A Metropolitan Tourism Region: The Example of Łódź - Liszewski , Stanisław (Turyzm/Tourism, 2005)
The author defines the concept of a metropolitan tourism region and presents a general model showing the trends and intensity of tourism and the development of tourism space. This is followed by the setting out of a general model using the example of the metropolitan tourism region of Łódź, and describing five development phases: initial, institutional, infilling, saturation and regression.